Rural-Urban Differences in Outcomes of Acute Cardiac Admissions in a Large Health Service - Shanathan Sritharan, BMed, MPH, MHLM; Bradley Wilsmore, BSc(Hons), MBBS, PhD; John Wiggers, BA(Hons), PhD; Lloyd Butel-Simoes, BMed; Kristy Fakes, B Med Sci (Path), MPH, PhD; Michael McGee, MBBS, MHLM; Rhonda Walker, MHS; Mikaela White, B Nurs; Lucy Leigh, B MedRadSci, B Math, PhD; Nicholas Collins, BMed; Andrew Boyle, MBBS, PhD; Aaron L. Sverdlov, MBBS, PhD; et al. (JACC: Advances)
Background: Cardiovascular disease (CVD) is a leading cause of morbidity and mortality and residing in a rural and remote region is associated with an increased risk. The impact of rurality on CVD outcomes needs to be fully elucidated. Objectives: The purpose of this study was to assess the difference in mortality, readmission within 30 days, total readmissions, survival, and total emergency department (ED) presentations following an index CVD admission among patients from rural or remote areas as compared to metropolitan areas. Methods: This retrospective observational study included all index hospitalizations with heart failure (HF), atrial fibrillation (AF), or acute coronary syndrome (ACS) within the Hunter New England region of Australia, between January 1, 2008, and December 31, 2021. Results: There were 27,995 ACS admissions, 15,586 HF admissions, and 16,935 AF admissions. Patients from a rural or remote area presenting with CVD presentations had increased 30-day readmission (OR: 1.19; P < 0.001), an increased number of readmissions (incident rate ratio: 1.19; P < 0.001), and more ED presentations (incident rate ratio: 1.39; P < 0.001) as compared to patients from metropolitan areas. This was consistent across patients presenting with ACS, HF, and AF. There was no difference in mortality (HR: 1.01; P = 0.515). However, in the ACS subgroup, there was increased mortality in the rural and remote population (HR: 1.05; P = 0.015). Conclusions: This study highlights the increased incidence of ED presentations and hospital readmissions, for those living in rural Australia, illustrating the disparity in health care provided, and the ongoing need for interventions that address poorer access to specialized health care in the early discharge phase of hospitalization.